Malignant melanoma of the rectum: a case report - Ferguson Adam; Semeraro David; Liptrot Sarah; Hurst Nicholas (Journal of Medical Case Reports, 2009)
Abstract Introduction Anorectal melanoma represents an unusual but important presentation of rectal malignancy. There have only been a few cases reported and the optimum management for this condition is still undecided, however, prompt diagnosis is essential. We have outlined current treatment options. Case presentation We report a case of malignant melanoma of the rectum in a 55-year-old Caucasian man presenting as an emergency with rectal bleeding. Biopsies were taken of the fleshy mass found on digital examination, which confirmed malignant melanoma. No distant metastases were found. He underwent an abdominoperineal resection. We report the surgical management of this rare and aggressive malignancy. Conclusion Treatment options for this condition are divergent. Surgical management varies from wide local excision to abdominoperineal resection. Clinical awareness in both medical and surgical clinics is required for prompt diagnosis and treatment.